Al-Hallaj - Xananta Zeres Ha’gai Br Sembiring; Nurul Hasanah Simamora; Nabila Syahlita Dewi; Muhammad Rafly; Muhammad Alfarizi Lubis (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
The research study conducted by this author was motivated by the existence of the teachings of al-Hallaj's philosophical Sufism, especially the hulul, which is often misunderstood and seen as a practice leading to apostasy and because the pioneer was executed on charges of apostasy. Al-Hallaj has been better known as a Sufi who violates religious boundaries (apostate). While some circles also judge, al-Hallaj's mistake, because he had opened up divine secrets, which should have been covered up. The method used in this research is library research, which is a study whose subject is library literature which is summarized through a book, journal and previous studies. The results of this study indicate that the specialty of Sufism in Islam is that with the approach of Sufism by the Sufis, Islamic teachings have succeeded in penetrating to various parts of the world, being accepted and embraced as a religion whose truth is believed to be true without violence and war. The controversy over the teachings of Al Hallaj is that Al Hulul, Nur Muhammad and the unity of all religions, which if heard or read at a glance, let alone the common people without thinking they can accept it outright, but if examined more deeply it will appear to be a teaching. which is misleading, because it contradicts the Qur'an al-Sunnah.